Professional Development and Training Programs for Elementary School Teachers in the Last Decade – A Systematic Literature Review - Ernamasari, Navalia Dewi; Marmoah, Sri (Universitas Batanghari Jambi, 2025)
Professional development for elementary teachers is vital for improving education quality and student outcomes. This systematic literature review synthesizes findings from 15 studies (2019-2025) on teacher training programs, focusing on their effectiveness, methodologies, and challenges. The analyzed studies, from Indonesia, Pakistan, and other international contexts, employed diverse methodologies including quasi-experimental, qualitative, and quantitative designs. The review finds that in-service training generally has a significant positive impact on teacher competency, pedagogical skills, and curriculum implementation, with evidence of statistically improved performance. However, effectiveness is moderated by contextual factors, necessitating programs that are context-sensitive and formative. A critical challenge is sustainability; without ongoing support, initial training benefits often diminish over time. The governance and structure of programs, alongside the integration of digital skills and STEM education, are identified as pivotal areas for development. Consequently, effective professional development must evolve beyond one-off sessions towards sustained, supportive, and contextually relevant initiatives. Future programs should incorporate long-term mentoring, feedback mechanisms, and tailored content to ensure lasting improvements in teaching practices and effectively address classroom challenges.